The impact of PECS II blockade in patients undergoing minimally invasive cardiac surgery—a prospective, randomized, controlled, and triple-blinded trial - Elisabeth Hoerner; Ottokar Stundner; Felix Naegele; Anna Fiala; Nikolaos Bonaros; Peter Mair; Johannes Holfeld; Lukas Gasteiger (Trials, 2023)
Abstract Background Classic neuraxial techniques, such as thoracic epidural anesthesia, or alternative approaches like the paravertebral block, are not indicated in cardiac surgery due to increased bleeding risk. To provide satisfactory analgesia without the need for excessive opioid use, novel ultrasound techniques gained popularity and are of growing interest. The pectoralis nerve block II (PECS II) has been shown to provide good postoperative analgesia in modified radical mastectomy and might also be suitable for minimally invasive cardiac surgery. Methods In a single center, prospective, triple-blinded, two-group randomized trial, 60 patients undergoing elective, unilateral minimal invasive cardiac surgery will be randomized to receive a PECS II with 30 ml of ropivacaine 0.5% (intervention group) or sodium chloride 0.9% (placebo group). The primary outcome parameter is the overall opioid demand given as intravenous morphine milligram equivalents (MME) during the first 24 h after extubation. Secondary endpoints are the visual analog scale (VAS) 2, 4, 6, 8, 12, and 24 h after extubation, the Overall Benefit of Analgesia Score (OBAS) after 24 h, the interval until extubation, and intensive care unit (ICU) discharge within 24 h, as well as the length of hospital stay (LOS). Discussion This prospective randomized, controlled, and triple-blinded trial aims to assess if a PECS II with ropivacaine 0.5% helps to decrease the opioid demand in the first 24 h and increases postoperative pain control after minimally invasive cardiac surgery. Trial registration www.clinicaltrialsregister.eu ; EudraCT Nr: 2021–005452-11; Lukas Gasteiger MD, November 18, 2021.